2020
DOI: 10.1111/jocd.13404
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a collagen hydrolysate and antioxidants‐containing nutraceutical on metrics of skin health in Indian women

Abstract: Background The skin’s aging process involves a decreased biosynthesis of extracellular matrix proteins (predominantly collagen) compounded by damage from environmental and intrinsic stressors. The Indian population is susceptible to skin damage given its geography and increasing urbanization or a genetic disposition. Previous studies have investigated nutrients such as collagen peptides, vitamins and phytonutrient‐rich botanical extracts for their individual benefits on skin. Aims This study examined the colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 52 publications
1
4
0
5
Order By: Relevance
“…Os anos de publicação dos artigos variaram entre 2007 e 2021. A maioria (92,3%; n= 12) dos artigos estava no idioma inglês (Lacroix et al, 2007;Costa et al, 2012;Bojanowski, 2013;Costa et al, 2015;Dumoulin et al, 2016;Decean et al, 2018;Motwani et al, 2020;Huber et al, 2021;Michailidis et al, 2021;Rafique et al, 2021;Xie et al, 2021;Yarovaya et al, 2021), enquanto que apenas um (7,9%) estava no idioma português (Costa et al, 2011).…”
Section: Resultsunclassified
“…Os anos de publicação dos artigos variaram entre 2007 e 2021. A maioria (92,3%; n= 12) dos artigos estava no idioma inglês (Lacroix et al, 2007;Costa et al, 2012;Bojanowski, 2013;Costa et al, 2015;Dumoulin et al, 2016;Decean et al, 2018;Motwani et al, 2020;Huber et al, 2021;Michailidis et al, 2021;Rafique et al, 2021;Xie et al, 2021;Yarovaya et al, 2021), enquanto que apenas um (7,9%) estava no idioma português (Costa et al, 2011).…”
Section: Resultsunclassified
“…The use of natural ingredients such as tomato extract or tomato seed oil in cosmetic products for skin care and health has also received popularity over the last few years [ 85 , 86 , 87 , 121 , 284 , 287 , 291 , 292 , 293 , 294 , 295 , 296 , 297 ]. Tomato seed oil has been extensively used in the production of cosmetic and personal care products such as anti-aging serums, body butter, sunscreens, and skin lightening cream due to its high linoleic acid, lecithin, antioxidant, and natural UV protection attributes [ 284 ].…”
Section: Health Effectsmentioning
confidence: 99%
“…Other reported benefits of tomato compounds for skin health include the protection against tick bites and heavy metal toxicity [ 64 , 121 , 292 , 296 , 299 ]. Boulanger et al showed that natural skin repellents made from eucalyptus, tomato, and coconut can protect against tick-borne infections such as Lyme disease [ 63 ].…”
Section: Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that oral supplementation with collagen hydrolysate and antioxidant-containing nutraceuticals significantly decreased wrinkle width, open pores, skin roughness, and the color of hyperpigmented blemishes, and enhanced skin hydration, firmness, elasticity, and barrier function, in female participants’ eye skin [ 124 ].…”
Section: Efficacy and Mechanisms Of Dietary Components In Mitigating Skin Photoaging: Animal And Human Evidencementioning
confidence: 99%